The Rotting Goddess: the Origin of the Witch in Classical Antiquity - Ezzy, Doug (Pomegranate, 2002)
The Rotting Goddess: the Origin of the Witch in Classical Antiquity by Jacob Rabinowitz Automedia: New Yo r k